2011
DOI: 10.1253/circj.cj-11-0465
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Aortic Dilatation or Dissection in Japanese Women With Marfan Syndrome

Abstract: Background: Aortic dilatation and dissection are severe complications of pregnancy that may cause maternal death. The purpose of the present study was to investigate risk factors for aortic dilatation or dissection in pregnant Japanese women with Marfan syndrome. Methods and Results:A total of 28 patients with Marfan syndrome were investigated retrospectively during pregnancy and after delivery at 1 institution. These patients were divided into 2 groups: those who experienced aortic dilatation or dissection (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The vessel wall can become weakened during pregnancy and remain weakened for up to 3 months postpartum. 25 A decrease in collagen synthesis, eosinophilic infiltration, excess progesterone, and fluctuating estrogen levels might contribute to the development of dissection. 23 An association between ritodrine and AMI suggests that increased stroke volume and shear forces are involved.…”
Section: Etiologymentioning
confidence: 99%
“…The vessel wall can become weakened during pregnancy and remain weakened for up to 3 months postpartum. 25 A decrease in collagen synthesis, eosinophilic infiltration, excess progesterone, and fluctuating estrogen levels might contribute to the development of dissection. 23 An association between ritodrine and AMI suggests that increased stroke volume and shear forces are involved.…”
Section: Etiologymentioning
confidence: 99%
“…In summary, the rates of aortic complications reported in prospective studies appear to reach on average 4.0% (3,19,41,53) and is 2-6% in large retrospective reports including 1,142 pregnancies (20,22,(53)(54)(55)(56)(57)(58). The expected rate of AoD is ranging from 1% in women with aortic diameter <40 mm to as much as 10% in high-risk patients (those with aortic root diameter >40 mm, rapid dilatation or previous dissection of the ascending aorta) (3,9,53,59).…”
Section: Risk For the Mothermentioning
confidence: 90%
“…Katsuragi et al clearly demonstrate that the aortic size index (diameter of the Valsalva/body surface area) is a better indicator than the absolute size. 7 They demonstrate that an aortic size index >25 mm/m 2 is a risk for an aortic event in pregnant Japanese women with MFS.…”
Section: Risk Of Cardiovascular Complicationsmentioning
confidence: 94%
“…Katsuragi et al report that FBN1 mutation was found more commonly in patients with aortic complications than in those without them, though the difference did not reach statistical significance. 7 Although more than 100 FBN1 mutations have been described in the literature, the identification of the type of mutation is still insufficient to predict the phenotype of MFS. 5 Moreover, the current screening techniques identify FBN1 mutations in at least 70% of patients with classic MFS.…”
Section: Significance Of Gene Analysis and Clinical Manifestationsmentioning
confidence: 99%